EL PERIODISMO LITERARIO O EL ARTE DE CONTAR NOTICIAS (De la Crítica, 2024)
The article presented here summarizes the different positions of authors who have addressed the issue of literary journalism, in this sense, the ideas about the points of union and break between journalism and literature are collected, making a brief tour from its origins to the present. Methodologically, it was a documentary review research. As conclusions we can say that journalism focuses on narrating facts and events in a real way, literature finds its delight in the fictional or recreational expression. This is one of the points with which both genres or trades are usually differentiated. Literary journalism is presented as a hybrid genre between journalism and literature, based on its ability to relate a true fact with a visible participation of the narrative self, and to cover a wide range of topics.